Consecutive labelings for two classes of plane graphs - Kathiresan Km.; Muthuvel S.; Nagasubbu V.N. (Utilitas Mathematica, 1999)
We describe consecutive labeling of type (1,0,0) for two families of plane graphs namely, Subdivision of ladders and Lotuses inside a circle.